Representation of Islamic symbols in Ms. Marvel series - Dimas Rheidzaky Fahrian; Yasmin Farani (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2023)
Ms. Marvel is an American television series based on the same-named Marvel Comics superhero. It is the nineteenthMarvel Cinematic Universe television series and the twelfth chapter of Phase Four. This study intended to find and analyze the Islamic symbols represented in Ms. Marvel series so that the writers could elucidate them. As this is qualitative research, the writers, who have role as the primary instruments, analyze the data which were downloaded from internet (Ms. Marvel series) and they found that Islamic symbols in them can be analyzed through verbal and nonverbal data. The analyzed verbal data consists of expressions such as assalamualaikum and walaikumsalam, whereas the nonverbal data, which are in the forms of symbols, consists of Islamic clothing and mosque. Based on the data, the nonverbal symbol is the most prevalent in the movie series.